Interior design features and emotional experiences of older adults in community day care centers: a qualitative study in China - Li, Lintong; Wang, Suhua; Mansor, Noranita; Azmi, Athira; Ye, Chun; Zhang, Jing (Routledge, 2026)
Despite growing attention to the emotional and psychological health of older adults, the interior environments of community day care centers still prioritize function and physical safety and lack a systematic mechanism to translate emotional needs into actionable design strategies. This study uses the three-level theory of emotional design (TTED) to build a validation pathway that links a systematic literature review with expert evidence. We first identified ten initial parameters from the literature. We then conducted semi-structured interviews with fifteen experts in China and applied Braun and Clarke’s six-phase thematic analysis in ATLAS.ti 24 to verify and refine the parameters. The results confirmed seventeen key interior design features organized into four emotion-oriented dimensions: aesthetic needs, physical environmental comfort needs, functional and usability needs, and emotional and reflective needs. The outcome is an expert-validated conceptual model with operational definitions that offers a practice-ready toolkit for emotionally sensitive interior design in community eldercare settings and a reusable indicator base for future quantitative studies and on-site evaluations. This model closes the gap between recognizing emotional needs and specifying implementable interior features and parameters, and it supports improvements in daily experience and emotional well-being for older adults in community-based adult day care centers (CADCs).